"Resilience amidst challenges": Healthcare users' experiences of access and utilisation of primary healthcare services during the COVID-19 pandemic in southwestern Uganda. - Rachel Kawuma; Joseph Katongole; Abdmagidu Menya; Winnie Eoju; Jonathan Kitonsa; Katherine Gallagher; Deborah Watson-Jones; Eugene Ruzagira (PLOS Global Public Health)
Primary healthcare (PHC) systems are the first point of contact for healthcare users and are critical for disease prevention and early treatment. The COVID-19 pandemic overwhelmed PHC systems globally, including in sub-Saharan Africa, significantly impacting access to essential services. We describe the experiences of community PHC users' accessing and utilizing health services at 15 purposively selected health centers during the COVID-19 pandemic in Masaka district, southwestern Uganda. A qualitative study (13th-August-2021-4th-November-2021) was embedded with in a large investigation evaluating the impact of COVID-19 on PHC services across three African regions. We conducted 28 in-depth interviews (IDIs) and 2 focus group discussions (FGDs) among adult (females and males) healthcare users (aged ≥18 years). Data was analyzed by themes and charted against the Andersen's Behavioral Model for healthcare utilization. The analysis revealed that structural adjustments to enforce COVID-19 protocols, such as handwashing stations and reduced waiting times, were viewed positively. Facilitators of healthcare access included community sensitization, positive attitudes of health workers, and users' determination despite movement restrictions. However, barriers included fear of infection, medication shortages, reduced clinic hours, and the prioritization of COVID-19 care over other services. Participants adapted by obtaining travel permission letters and using herbal remedies when conventional care was inaccessible. Our key finding is that despite significant disruptions to PHC services during the COVID-19 pandemic, healthcare users demonstrated resilience in accessing care. However, systemic challenges, such as workforce shortages and limited essential medical supplies, highlighted vulnerabilities within the PHC system. Addressing these structural barriers and investing in more resilient and adaptive healthcare systems is crucial for ensuring equitable access to essential health services during future public health crises.